2019
DOI: 10.1109/tcsii.2019.2893533
|View full text |Cite
|
Sign up to set email alerts
|

70% Decrease of Hot-Spotted Photovoltaic Modules Output Power Loss Using Novel MPPT Algorithm

Abstract: The phenomenon of 'Hot-spotting' within photovoltaic (PV) panels, where a mismatched cell/cells heats up, leads to reliability and efficiency issues. In this paper, a novel maximum power point tracking (MPPT) algorithm is developed to compensate for hot-spotted PV module effects, thus increasing the output power and improving reliability. The MPPT algorithm implements two mitigation processes; the first to identify the optimum power-voltage (P-V) curve to track the global maximum power point (GMPP). The second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…In this arrangement, the fuel cell must comprise a control system (with stability mode controller) to connect quickly and control the fuel cell's current flow into the DC-DC converter, followed by a DC-AC inverter linked with the wheel drive machinery. Here, the DC-DC converter must act unidirectional, where no feedback/reversed current passes into the fuel cell [8,9]. It is also worth noting that current fuel cell EV models follow the configuration as in Fig.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this arrangement, the fuel cell must comprise a control system (with stability mode controller) to connect quickly and control the fuel cell's current flow into the DC-DC converter, followed by a DC-AC inverter linked with the wheel drive machinery. Here, the DC-DC converter must act unidirectional, where no feedback/reversed current passes into the fuel cell [8,9]. It is also worth noting that current fuel cell EV models follow the configuration as in Fig.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, M. Dhimish. [19], proposed suitable method improves the output power of hot-spotted PV module at least by 70%. The method uses a modified maximum power point tracking (MPPT) algorithm which is skilled of determining the amount of current and voltage loss for hot-spotted PV modules, subsequently, increasing the output power production.…”
Section: Existing Hot-spots Mitigating Techniquesmentioning
confidence: 99%
“…For serially connected PV system, shading, such a s birds, tree shadows, is a problem since the shaded PV module reduces the output whole string of PV modules [17][18][19]. The excess power from the unshaded PV module is dissipated in the shaded PV module and it is shown that temperature of the shaded PV module or cell rises as hot spot [20][21][22]. Until now, research on the shaded PV modules or 1030 cells has been mainly on the performance of the whole PV system, and there has been little analysis on the circuit and power dissipation of each PV module [23][24][25].…”
Section: Introductionmentioning
confidence: 99%